Загальні положення оскарження та розгляду скарг у досудовому провадженні - Пшенічко, Станіслав Олексійович; Пшеничко, Станислав Алексеевич; Pshenichko, Stanislav (Одеса : Юрид. л-ра, 2012)
The article deals with t h e issues r e l a t e d to t h e definition of t h e general provisions of appeal as t h e criminal procedure of t h e complaint a n d to t h e general provisions of t h e prosecutor and t h e investigating m a g i s t r a t e review.
Пшенічко С. О. Загальні положення оскарження та розгляду скарг у досудовому провадженні / С. О. Пшенічко // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 741-748.
Keywords: скарга; оскарження; досудове провадження; прокурор; слідчий суддя; жалоба; обжалование; досудебное производство; следственный судья; complaint; appeal; pre - trial proceedings; prosecutor; investigаting magistrate